Slow Binocular Rivalry as a Potential Endophenotype of Schizophrenia - Xiao, Guixian (Front Neurosci, 2018)
Objectives: Binocular rivalry is a typical example of bistable perception that arises when two monocular images are simultaneously presented to each eye. Binocular rivalry is a heritable perceptual cognitive function that is impaired in patients with schizophrenia (SZ). Despite its potential suitability as a visual endophenotype, binocular rivalry has hardly been studied in the unaffected siblings of schizophrenia (SIB). There is also little research about whether binocular rivalry is a potential visual endophenotype between SZ and SIB. Methods: In our cross-sectional study, we included 40 SZ and their unaffected SIBs, as well as 40 age- and sex-matched healthy controls (HC). All subjects underwent the binocular rivalry test, the Positive and Negative Syndrome Scale (PANSS) and a battery of cognitive neuropsychological assessments evaluating attention, memory and executive function domains. Results: Our results demonstrate that the switching rate in SZ was significantly slower than in HC (p < 0.001), and compared to the SIB, the mean alternation rates were significantly different (p < 0.01). Moreover, there was a significant difference in mean switching rate between the SIB and the HC (p < 0.001). There was no significant correlation between the alternation rate of binocular rivalry and these cognitive tasks and the PANSS scores. Conclusion: The present study shows that SZ and SIB both exhibit changes in binocular rivalry, with SIB exhibiting intermediate performance compared with that of SZ and the HC. This supports the claim that the switching rate for SZ differs from that of SIB and suggests that binocular rivalry may qualify as a visual endophenotype for SZ.